A strategic plan for the Davao Kirsti's Pawnshop Corporation - Bardilas, Marites P.; Soledad, Miguel D.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2010)
The focus of this Policy and Strategic Planning paper is the Davao Kirsti?s Pawnshop Corporation owned and managed by the Hao?s. The company is engaged in pawnshop operations with 18 branches in Davao City and one branch in Panabo City. The company?s long term goal is to open more branches outside Davao City. The strategic management framework of Fred David is used to evaluate the internal and external environment of the pawnshop industry; identify the long term objectives of the company; generate, evaluate and implement its strategies; measure and evaluate performance. The functional units taken into consideration include the organization and human resource, operations, marketing and finance. The company both responds satisfactorily to its internal and external environment based on the results of the External Factor Evaluation (EFE) Matrix and the Internal Factor Evaluation (IFE) Matrix. The strengths identified in the company include active participation of the family members, multi-tasking approach, promotional activities, branches located in strategic locations and in the malls in Davao City, profitability and liquidity of the company. The company?s weaknesses include the issue on management succession; lack of training and development programs and absence of salary structure; non-acceptance of other items for pawn; low turn-over or asset utilization ratio; and conservatism in borrowing. Among the three strategic options, market development, was chosen for implementation since this is aligned to the company?s goal to expand outside Davao City. Towards the direction of market development, there is a need to meet its primary prerequisite that is the need to strengthen its organization and compensation and benefits review and implementation. In the next five years, the strategic outcomes identified by this paper shall be: 1) re-organization of the company, implementation of salary/pay structure and merit increase, geographical expansion in Tagum City and General Santos City, and sustainable growth for the company.
Thesis (Master in Management)--University of the Philippines Mindanao, January 2010.